Intramedullary nail fixation versus open reduction and internal fixation for treatment of adult diaphyseal forearm fractures: a systematic review and meta-analysis - McKenna W. Box; Samuel D. Stegelmann; Grayson A. Domingue; Monica E. Wells; Neil J. Werthmann; Cornelis J. Potgieter; John T. Riehl (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Diaphyseal radius and ulna fractures require surgical fixation in adults. Open reduction and internal fixation (ORIF) have been considered the gold standard of treatment. The recent development of an interlocking intramedullary nail (IMN) has provided an alternative treatment method for these fractures. The objective of this meta-analysis is to compare the outcomes and complications of IMN versus ORIF for diaphyseal forearm fractures in adults. Methods MEDLINE and Embase were searched from January 1, 2000, through January 7, 2024. All English-language studies were included comparing radiographic and functional outcomes for interlocking IMN fixation and ORIF of diaphyseal forearm fractures in adults (age ≥ 18 years). Study demographics, fracture data, functional outcomes, radiographic outcomes, and complications were extracted. Study quality was determined using the ROBINS-I criteria for cohort studies and the Cochrane risk of bias 2.0 (RoB 2) tool for randomized controlled trials. Meta-analysis of included studies used odds ratios and standardized mean difference when appropriate. Data was analyzed using subgroups of all diaphyseal fractures (including isolated radius or ulna fractures) and those with BBFFs. Results Nine studies were included for analysis. There were 42 isolated radius, 80 isolated ulna, and 116 both-bone fractures (BBFF) treated with IMN and 36 radius, 81 ulna, and 116 both-bone fractures treated with ORIF. Compared to ORIF, IMN of diaphyseal forearm fractures appeared to be associated with shorter operative times and a lower overall complication rate. Time-to-union and the rate of nonunion following IMN were similar to ORIF. According to the Grace–Eversmann score, functional outcomes tended to be better following IMN, but DASH scores were similar between fixation strategies. Conclusions Our findings suggest that interlocking IMN can be a safe and effective treatment option for simple and complex diaphyseal forearm fractures in adults. Further high-quality studies are needed to define indications for treating diaphyseal fractures with an interlocking IMN. Level of Evidence Therapeutic Level IV.